FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI (STUDI PADA KANTOR PELAYANAN PAJAK PRATAMA JAKARTA CENGKARENG) - Rr Anggita Kususmaswara; Y. Agus Bagus Budi N (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2011)
This study tried exploring whether factors such as equality, tax penalties and fines, self assessment system and public trust to government can influence compliance (tax) significantly for individual resident taxpayers. In term of state budget, corporate taxpayers has long been a high concernfrom the government. This is not a mistake. But this is also an indication that the government has not made comprehensive framework on how to attract individuals becoming taxpayers. Even the study found the relationship between the factors tested toward the compliance (tax), the government should keep in mind that there are many factors that must be considered and studied thoroughly.